2020
DOI: 10.1242/dev.196618
|View full text |Cite
|
Sign up to set email alerts
|

Asynchrony of ovule primordia initiation in Arabidopsis

Abstract: Plant ovule initiation determines the maximum of ovule number and has a great impact on the seed number per fruit. The detailed processes of ovule initiation have not been accurately described although two connected processes, gynoecium and ovule development, have been investigated. Here we report that ovules initiate asynchronously. The first group of ovule primordia grows out, the placenta elongate, the boundaries of existing ovules enlarge and new group of primordia initiates from the boundaries. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 95 publications
(143 reference statements)
4
59
0
Order By: Relevance
“…Next, we dissected ovules from pistils of various lengths, determined the stage of the ovules for each pistil, and used the pistil growth curve for an estimate of the duration of the different ovule stages (see Materials and methods). It was previously noticed that early stage ovules do not develop synchronously within a pistil ( Schneitz et al, 1995 ; Wolny et al, 2020 ; Yu et al, 2020 ). In line with these results, we observed ovules of different stages within a given pistil ( Supplementary file 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we dissected ovules from pistils of various lengths, determined the stage of the ovules for each pistil, and used the pistil growth curve for an estimate of the duration of the different ovule stages (see Materials and methods). It was previously noticed that early stage ovules do not develop synchronously within a pistil ( Schneitz et al, 1995 ; Wolny et al, 2020 ; Yu et al, 2020 ). In line with these results, we observed ovules of different stages within a given pistil ( Supplementary file 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…BRs affect ovule number and gynoecium size by modulating gene expression, like HLL and ANT , which exhibit similar effects on primordial ovule growth [ 12 , 14 , 62 ], and the AP2 gene, which affects ovule number determination and developmental specificity of the floral organ. As expected, the loss of function ant mutation affects carpel margin meristem and placenta development, resulting in abnormal lateral organs, and reduced fertility and number of ovules [ 31 , 41 , 106 ].…”
Section: Molecular Network Of Ovule Number Regulationmentioning
confidence: 99%
“…As expected, the loss of function ant mutation affects carpel margin meristem and placenta development, resulting in abnormal lateral organs, and reduced fertility and number of ovules [ 31 , 41 , 106 ]. Previous studies have demonstrated that BR affects ovule number via transcriptional control of primary ovule development genes ANT , HLL , and AP2 [ 12 , 50 ]. BZR1 activity was correlated with the upregulation of ANT and HUL genes, showing that BR signaling positively influences ovule number [ 50 , 57 ].…”
Section: Molecular Network Of Ovule Number Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…LEC2 is a positive regulator of selenium-induced YUC-mediated auxin biosynthesis in Arabidopsis thaliana somatic embryogenesis [81,82]. The overexpression of miR167c inhibited the formation of selenium and increases the expression of LEC2 [12], and at the same time interfered with PIN-FORMED1 (PIN1) in cell membrane of embryogenic callus affected auxin transport [83][84][85]. miR167 targeted ARF6 and ARF8, effects on auxin synthesis and local auxin transport in embryogenic callus, thus regulating Arabidopsis thaliana somatic embryogenesis.…”
Section: Mir167 Regulates Plant Embryo and Seed Developmentmentioning
confidence: 99%